2011
DOI: 10.1007/s13197-011-0463-4
|View full text |Cite
|
Sign up to set email alerts
|

Precooking processing of bamboo shoots for removal of anti-nutrients

Abstract: Bamboo shoots being low in fat, high in dietary fiber and rich in mineral content, like an ideal vegetable have been used traditionally. Besides nutrients, bamboo shoots also contain lethal concentration of the anti-nutrient (cyanogen) that need to be removed before human consumption. Therefore an attempt has been made to find out the best processing method for confiscation of cyanogens. B. bambos, B. tulda, D. strictus and D.asper were selected for the study. Fresh and processed bamboo shoots were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
(10 reference statements)
0
40
1
Order By: Relevance
“…The authors state that there is no single specific treatment for all bamboo species which removes cyanogens with minimum loss of nutrients. Although earlier studies had suggested that addition of NaCl to the boiling water could speed up the decrease of cyanogens, a clear effect of NaCl was not observed in the study by Pandey and Ojha ().…”
Section: Assessmentmentioning
confidence: 69%
See 1 more Smart Citation
“…The authors state that there is no single specific treatment for all bamboo species which removes cyanogens with minimum loss of nutrients. Although earlier studies had suggested that addition of NaCl to the boiling water could speed up the decrease of cyanogens, a clear effect of NaCl was not observed in the study by Pandey and Ojha ().…”
Section: Assessmentmentioning
confidence: 69%
“…However, they also contain cyanogens, primarily taxiphyllin (Brimer, ) at levels which vary considerably between bamboo species growing in different agroclimatic regions. Pandey and Ojha () studied the decrease of cyanogens in shoots from four bamboo species when boiled in water with different concentrations of NaCl (0, 1, 5 and 10%) for various length of time (10, 15, 20, 25 min). A reduction of about 80–95% of the cyanogens was achieved in most cases, which was, however, accompanied by significant losses of proteins and micronutrients.…”
Section: Assessmentmentioning
confidence: 99%
“…Due to such high profile of nutrition, bamboo shoot is considered as an ideal healthy vegetable. But, bamboo shoots also contain lethal concentration of the anti-nutrient (cyanogen) that can be minimized by boiling it with NaCl solution (Pandey and Ojha 2011;Rana et al 2012). In the Northeastern states of India, bamboo shoots are largely sold in the unprocessed form.…”
Section: Introductionmentioning
confidence: 99%
“…Brine preservation caused a drastic increase in the Na content (18.79 g/100 g, dry weight; P < .05) followed by boiling (0.16 g/100 g, dry weight) and fermentation (0.07 g/100 g, dry weight). Pandey and Ojha [16] also reported a significant increase in sodium content when shoots of four bamboo species (Bambusa bambos, Bambusa tulda, Dendrocalamus asper, and Dendrocalamus strictus) were boiled in 5% brine solution for 10 min, with the highest increase in the shoots of B. tulda followed by D. asper, D. strictus, and B. bambos. Increase might be due the absorption of sodium and chloride content from the preserving medium.…”
Section: Resultsmentioning
confidence: 92%